Reading with drama: relations between texts, readers and experiences. (3rd March 2021) - Medina, Carmen Liliana; Perry, Mia; Lee, Bridget Kiger; Deliman, Amanda
Abstract: This article explores the intersections of drama and reading, specifically focusing on approaches that are situated within "drama in education." Supported with a retrospective analysis, this article portrays the research, related practice and possible futures in drama education in relation to literacy and in particular to reading fiction as meaning making practice. This study is situated in a reassertion of the value of relational literacies through imaginative practices that dramatic modes generate and support. The article disrupts common misconceptions about the purposes and effects of drama in reading and establishes prominent research discourses and definitions across the history of drama and reading practices. By locating paradigmatic and practical opportunities in our analysis of contemporary research, we bring visibility to the intricacies of drama in education as a generative pedagogy in reading as relational meaning making work.